2015
DOI: 10.1002/ijc.29887
|View full text |Cite
|
Sign up to set email alerts
|

mTOR inhibitor‐induced interstitial lung disease in cancer patients: Comprehensive review and a practical management algorithm

Abstract: Mammalian target of rapamycin inhibitors (mTORi) have clinically significant activity against various malignancies, such as renal cell carcinoma and breast cancer, but their use can be complicated by several toxicities. Interstitial lung disease (ILD) is an adverse event of particular importance. Mostly, mTORi-induced ILD remains asymptomatic or mildly symptomatic, but it can also lead to severe morbidity and even mortality. Therefore, careful diagnosis and management of ILD is warranted. The reported incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 93 publications
4
73
0
3
Order By: Relevance
“…The rate of severe pneumonitis (grade ≥3) with apitolisib was 8%, which is higher than reported for PI3K and dual mTOR inhibitors (18-21, 37). This is presumably related to mTOR inhibition, correlates with the frequency seen with rapalogs (38), and suggests increased mTOR pathway blockade compared to published dual PI3K/mTOR inhibitors. Given these toxicities and one grade 5 colitis on the 50 mg 28/28 schedule, the RP2D was 40 mg continuous QD oral dosing on a 28/28 schedule.…”
Section: Discussionmentioning
confidence: 68%
“…The rate of severe pneumonitis (grade ≥3) with apitolisib was 8%, which is higher than reported for PI3K and dual mTOR inhibitors (18-21, 37). This is presumably related to mTOR inhibition, correlates with the frequency seen with rapalogs (38), and suggests increased mTOR pathway blockade compared to published dual PI3K/mTOR inhibitors. Given these toxicities and one grade 5 colitis on the 50 mg 28/28 schedule, the RP2D was 40 mg continuous QD oral dosing on a 28/28 schedule.…”
Section: Discussionmentioning
confidence: 68%
“…123,124 Additionally, more than 10% of patients taking mTOR inhibitors experience some grade of pulmonary toxicity. 125,126 Some of the pulmonary complications include pneumonitis, interstitial lung disease and opportunistic respiratory infections, but the mechanisms are not completely understood. Rapa-mycin can cause pulmonary fibrosis when used with lung transplantation, which might be related to rapamycin’s ability to induce epithelial-mesenchymal transition in bronchial or pulmonary cells.…”
Section: Implication Of Targeting Mtor Signaling In Lung Cancermentioning
confidence: 99%
“…The issue of EVR-related interstitial pneumonia, which was reported in 2% to 5% of patients on EVR in the H2304 and PROTECT trials, 13,14,17,18,30 was not addressed because its incidence is lower than what was reported in other solid organ transplant populations (ie, kidney) or in cancer patients. 62,63 …”
Section: Discussionmentioning
confidence: 99%